The impact of biodiesel demand on the Malaysian palm oil market : a combination of econometric and system dynamics approach. - Applanaidu, Shri Dewi; Mohamed Arshad, Fatimah; Shamsudin, Mad Nasir; Yusop, Zulkornain (2010)
In the last few years, against the background of increasing concerns regarding the energy supply security as well as environmental concern has increased the interest for renewable energy sources. This have resulted in some countries to look for bio-based alternative energies which lead to the increase in demand for bio-based feedstocks such as palm and rapeseed oil (for bio-diesel) and sugar cane and corn (for ethanol). Due to the increased importance of biodiesel in Malaysia and elsewhere, the impact of this new demand has added a new dimension in the fats and oils market model particularly palm oil. This paper seeks to examine the impact of biodiesel demand on Malaysian palm oil industry. This study attempts to integrate the econometric and system dynamics approaches in modeling the palm oil market in Malaysia. One of the problems with the econometric modeling is its inability to deal with the interrelationships of the real world scenario if there is no data. The system dynamics on the other hand provides an alternative platform to handle multi-loop and nonlinear feedback system that exists in a complex market such as palm oil. It analyses the behaviour of the commodity system by identifying the cause and effect relationships and feedback control that creates the dynamics in the system. The system elements included in the model are, supply, domestic demand, export demand, world price, domestic price and stock. The model in general is able to capture the complex interdependencies that exist in the system and it can be used to study the effects of changes in one or more controllable variables on the performance of the system.